Citrullus colocynthis Oil as Biofuel and its Performance in Engines: A Review - Jain, Nirupa; Sangwa, Narpat Ram; Mathur, Yash Bansi; Kumar, Krishan; Sharma, Anshumala (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2020)
Fossil fuel is not a renewable source of energy and its stocks will exhaust shortly. There is a need to explore the possibility of new sources of fuel, which may be used in existing vehicles so that there is no crisis in the future. The need for a clean source of energy has been highlighted by SDG 7. A large number of research studies have been carried out in this sector to explore the potential in the possibilities of the development of biofuel. Various vegetable oil has been tried and explored. Citrullus colocynthis oil has also been studied for biofuel. Citrullus colocynthis is called Thumba in India. Research studies have confirmed that it can be an important source of biofuel. Research studies have found that Citrullus colocynthis oil can be blended with diesel and can be used in existing engines. Considering the need for biodiesel, this review paper identifies previous studies on this resource to meet the growing demand for clean energy resources. How to cite this article:  Jain N, Sangwa NR, Mathur YB et al. Citrullus colocynthis Oil as Biofuel and its Performance in Engines: A Review. J Adv Res Alt Energ Env Eco 2020; 7(4): 10-20.